REKONSTRUKSI PROSES PEMBELAJARAN BAHASA ARAB PERSPEKTIF AL-QUR’AN - Hasanah, Mamluatul; Sari, Risna Rianti (Arabi : Journal of Arabic Studies, 2021)
Concerns to the balance of achieving knowledge, skills, and literacy competencies are less noticed in the Arabic learning process. Therefore, it is necessary to reconstruct the learning process as a solution. This study aims to carry out the reconstruction by using the Quran as the primary source. Verses related to the development of human language are used as the main data analyzed using the historical scientific approach of Ibn Faris and Krippendorf content analysis. As an analytical perspective, three literacy theories are used, namely The Four Resources Model, The Literacy Triptyche, and the Balance Literacy Model. There are five phases of human language development according to the Quran, namely the imitation phase, the perception phase of reason, the evolutionary phase of language and abstraction, the hubuth phase, and the isthifa phase. These phases, when elaborated into a learning cycle, become a modeling cycle, building context, constructing texts either guided or independently, evaluating text constructs, and critical texts. The imitation phase will lead language learners to master knowledge competencies. The perception phase of reasoning can lead to the achievement of skill competence. Literacy competence can be achieved through all cycles; even in the hubuth and isthifa phase, language learners can achieve critical literacy competence.